Peran External Assurance sebagai Pemoderasi pada Pengaruh Good Corporate Governance terhadap Kualitas Laporan Keberlanjutan di ASEAN - Aulia, Nida; Sari, Ratna Candra (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2026)
This study aims to analyze the influence of good corporate governance (GCG) on the quality of sustainability reporting in ASEAN-5 companies. The primary focus of this study is to examine how the characteristics of the audit committee, independent commissioners, gender diversity on the board, and the presence of external assurance moderate the quality of sustainability reports. The findings of this study are expected to provide practical contributions to companies in enhancing transparency, credibility, and accuracy of sustainability reports, while enriching academic literature in the fields of corporate governance and sustainability. The research method used is a quantitative approach with a causal-comparative research design. The research was conducted on companies listed on the ASEAN stock exchange from 2019 to 2022. The research population consisted of 745 companies and the sample consisted of 221 companies. The sampling technique used was purposive sampling. This study utilized secondary data obtained from database Bloomberg and the World Bank. Data analysis was conducted using panel data regression with Statistical Software. The results of this study indicate that independent and gender-diverse commissioners have a positive and significant effect on the quality of sustainability reports. However, the audit committee shows no positive effect on the quality of sustainability reports. Furthermore, the role of external assurance weakens the relationship between independent commissioners and gender diversity on sustainability report quality.